Firms in international trade: Importers and exporters heterogeneity in Italian manufacturing data - Davide Castellani; Francesco Serti; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
This paper offers a portrait of Italian firms that trade goods. Combining data on firms' structural characteristics and economic performance with data on their exporting and importing activity, we uncover evidence supporting recent theories on firm heterogeneity and international trade, together with some new facts. In particular, we find that importing can be as important as exporting as a source of firm heterogeneity. First, we document that trade is more concentrated than employment and sales, and we show that import is even more concentrated than export both within sectors and along the sector and country extensive margins. Second, while supporting the fact that firms involved in both importing and exporting (two-way traders) are the best performers, we also find that firms involved only in importing activities perform better than those involved only in exporting. We submit that this may have to do with being mainly importers of high-tech capital goods. Third, the performance premia of internationalized firms correlate relatively more with the degree of geographical and sectoral diversification of imports.
Keywords: F10; F16; J21; 330; heterogeneous firms; exports; imports; Außenhandelssektor; Export; Import; Unternehmenskonzentration; Konzentrationsindex; Produktivität; Unternehmenserfolg; Italien